2012
DOI: 10.3233/jad-2011-110713
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Rapid Cognitive Decline in Community-Dwelling Patients with Alzheimer's Disease

Abstract: Weight loss is a frequent complication of Alzheimer's disease (AD) and a strong predictor of adverse outcomes in patients suffering from this disease. The aim of this study was to determine whether weight loss was a predictor of rapid cognitive decline (RCD) in AD. Four hundred fourteen community-dwelling ambulatory patients with a diagnosis of probable AD and a Mini-Mental State Examination (MMSE) score between 10 and 26 from the REAL.FR (REseau sur la maladie d'ALzheimer FRançais) cohort were studied and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 30 publications
3
99
0
4
Order By: Relevance
“…Given that our sample was selected to have no serious diseases and the statistical modeling has controlled for disease history, this small proportion of the sample could have suffered from malnutrition, as indicated by their relatively lowest CBMI. The finding was consistent with studies that examined the relation of nutrition to cognitive functions in the older adults [15,[18][19][20]29] and findings that overweight is unnecessarily related to impaired CF [30]. There are two possible explanations for their underweight.…”
Section: Discussionsupporting
confidence: 79%
“…Given that our sample was selected to have no serious diseases and the statistical modeling has controlled for disease history, this small proportion of the sample could have suffered from malnutrition, as indicated by their relatively lowest CBMI. The finding was consistent with studies that examined the relation of nutrition to cognitive functions in the older adults [15,[18][19][20]29] and findings that overweight is unnecessarily related to impaired CF [30]. There are two possible explanations for their underweight.…”
Section: Discussionsupporting
confidence: 79%
“…It is reported that the onset of poor nutrition may be even before classical symptoms of dementia (1,2). It is crucial to screen these patients for malnutrition because poor nutrition is associated not only with a faster progression of dementia but also with adverse health problems (2,6,9,10). The MNA test is generally used to assess malnutrition in outpatient elderly (8).…”
Section: Discussionmentioning
confidence: 99%
“…Poor nutrition is also associated with worse cognition and functionality in these patients (5). Malnutrition is associated with poorer prognosis and adverse health problems in patients with dementia (2,6). Although the association of malnutrition with dementia is a well-known issue, studies involving community-dwelling AD patients from different populations are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with AD have a worse nutritional status compared to others and usually suffer from malnutrition and weight loss [8,9]. In addition, weight loss was reported to predict rapid cognitive decline in AD patients [10,11]. Consequently, treatment of weight loss and malnutrition may be important to decrease the risk of AD.…”
Section: Introductionmentioning
confidence: 99%